Navigating stress, anxiety, and mentorship: Challenges for students working on dissertations in the pandemic era - He, Chen Yu (Journal of Professional Teacher Education, 2024)
PhD students often encounter significant challenges, stress, and anxiety throughout their academic journey, particularly in their final year. This study explores the common difficulties faced by PhD students conducting thesis research at Chinese universities, focusing on their experiences with online supervision during the COVID-19 pandemic. A survey was conducted with ten full-time PhD students from selected Chinese universities, utilizing a combination of scaled, closed, and open-ended questions. The results indicate that students faced considerable challenges during online supervision, mainly due to inadequate funding and irregular, delayed supervisor feedback. Significant sources of stress and anxiety included thesis writing, supervisor relationships, and socioeconomic issues. However, adequate supervision, timely feedback, and purposeful guidance were found to mitigate these challenges. The study concludes that online supervision during the pandemic has intensified the difficulties faced by PhD students, negatively impacting the quality of their research and completion rates. To improve the supervision process, students recommended enhancing communication, increasing supervisor accessibility, and providing prompt feedback to support timely dissertation completion.